The Effect of Digital Marketing, Word of Mouth, Brand Trust and Image on the Purchase Decision - Mukti, Fauzan Olga Dwi; Isa, Muzakar (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Social media has become a very important tool in the business world, especially in marketing activities. One strategy that is often used is Social Media Marketing, which aims to introduce products or services, provide and share information, and increase sales at a relatively low cost. With these benefits, this study aims to measure the role of digital marketing, word of mouth, product trust, and brand image on purchasing decisions, especially on the Es Teh Indonesia brand. This study was conducted using a purposive sampling approach, where data was collected boldly from people around the Surakarta area. The data obtained were then analyzed using multiple linear regression methods, with the help of SPSS software. The results of the analysis showed that each variable tested, namely digital marketing, word of mouth, product trust, and brand image, had a positive influence on the final customer purchasing decision. This finding emphasizes the importance of digital marketing strategies and word of mouth in shaping product trust and brand image, which ultimately encourages consumers to make purchases. This conclusion provides insight for companies to focus on developing effective marketing strategies to improve purchasing decisions